Breast health health care - Stoppard, Miriam (Dorling Kindersley, 1998)
An authoritative guide to all aspects of breast care for women at every stage of life, from puberty to menopause and beyond, this text presents up-to-date information on routine screening and the full range of treatments for breast conditions